Short-, Mid-, and Long-Term Effect of Granulocyte Colony-Stimulating Factor/Stem Cell Factor and Fms-Related Tyrosine Kinase 3 Ligand Evaluated in an In Vivo Model of Hypoxic-Hyperoxic Ischemic Neonatal Brain Injury. (13th March 2019) - Posod, Anna; Wegleiter, Karina; Neubauer, Vera; Urbanek, Martina; Huber, Eva; Kiechl-Kohlendorfer, Ursula; Keller, Matthias; Griesmaier, Elke
Abstract : Hematopoietic growth factors are considered to bear neuroprotective potential. We have previously shown that delayed treatment with granulocyte colony-stimulating factor (G-CSF)/stem cell factor (SCF) and Fms-related tyrosine kinase 3 ligand (FL) ameliorates excitotoxic neonatal brain injury. The effect of these substances in combined-stressor neonatal brain injury models more closely mimicking clinical conditions has not been investigated. The aim of this study was to assess the short-, mid-, and long-term neuroprotective potential of G-CSF/SCF and FL in a neonatal model of hypoxic-hyperoxic ischemic brain injury. Five-day-old (P5) CD-1 mice were subjected to unilateral common carotid artery ligation and subsequent alternating periods of hypoxia and hyperoxia for 65 minutes. Sixty hours after injury, pups were randomly assigned to intraperitoneal treatment with (i) G-CSF (200 μ g/kg)/SCF (50 μ g/kg), (ii) FL (100 μ g/kg), or (iii) vehicle every 24 hours for three or five consecutive days. Histopathological and functional outcomes were evaluated on P10, P18, and P90. Baseline outcome parameters were established in sham-treated and healthy control animals. Gross brain injury did not significantly differ between treatment groups at any time point. On P10, caspase-3 activation and caspase-independent apoptosis were similar between treatment groups; cell proliferation and the number of BrdU-positive vessels did not differ on P18 or P90. Neurobehavioral assessment did not reveal significant differences between treatment groups in accelerod performance, open field behavior, or novel object recognition capacity on P90. Turning behavior was more frequently observed in G-CSF/SCF- and FL-treated animals. No sex-specific differences were detected in any outcome parameter evaluated. In hypoxic-hyperoxic ischemic neonatal brain injury, G-CSF/SCF and FL treatment does not convey neuroprotection. Prior to potential clinical use, meticulous assessment of these hematopoietic growth factors is mandated.